Characterization of antibiotic resistance in commensal bacteria from an aquaculture ecosystem - Huang, Ying; Zhang, Lu; Tiu, Laura; Wang, Hua H. (Frontiers in Microbiology, 2015)
The objective of the study was to improve understanding of antibiotic resistance (AR) ecology through characterization of antibiotic resistant commensal isolates associated with an aquaculture production system. A total of 4767 isolates non-susceptible to sulfamethoxazole/trimethoprim, tetracycline, erythromycin, or cefotaxime, originated from fish, feed, and environmental samples of an aquaculture farm with no known history of antibiotic applications were examined. Close to 80% of the isolates exhibited multi-drug resistance in media containing the corresponding antibiotics, and representative AR genes were detected in various isolates by PCR, with feed isolates had the highest positive rate detected. Identified AR gene carriers involve 18 bacterial genera. Selected AR genes led to acquired resistance in other bacteria by transformation. The AR traits in many isolates were stable in the absence of selective pressure. AR-rich feed and possibly environmental factors may contribute to AR in the aquaculture ecosystem. For Minimum Inhibitory Concentration test, Brain Heart Infusion medium was found more suitable for majority of the bacteria examined than cation-adjusted Mueller Hinton broth, with latter being the recommended medium for clinical isolates by standard protocol. The data indicated a need to update the methodology due to genetic diversity of microbiota for better understanding of the AR ecology.